High‐speed reflectance confocal microscopy of human skin at 1251–1342 nm. Issue 4 (16th March 2023) - Ryu, Jiheun; Kang, Dongkyun; Kim, Junyoung; Chung, Anita; Grant, Catriona N.; Ryan, Emily; Barrios, Amilcar; Osman, Hany; Tearney, Guillermo J.
Abstract: Objectives: Reflectance confocal microscopy (RCM) is an imaging method that can noninvasively visualize microscopic features of the human skin. The utility of RCM can be further improved by increasing imaging speed. In this paper, we report high‐speed RCM imaging of human skin with a frame rate that is over 10 times faster and an area imaging rate that is 6–9 times faster than those of commercially available RCM devices. Methods: The higher imaging speed was achieved using a high‐speed RCM technique, termed spectrally encoded confocal microscopy (SECM). SECM uses a diffraction grating and a high‐speed, wavelength‐swept source to conduct confocal imaging at a very high rate. We developed a handheld SECM probe using a scanned‐grating approach. The SECM probe was used in conjunction with a wavelength‐swept source with a spectral band of 1251–1342 nm. Results: The SECM probe achieved high lateral resolution of 1.3–1.6 µm and an axial resolution of 3.5 µm. SECM images of the human skin (image size = 439 × 439 µm 2 ) obtained at 100 frames/s clearly show previously reported RCM features of the human skin in vivo with adequate image quality. The fast imaging speed allowed for the rapid acquisiton of volumetric SECM image data (200 frames covering a depth range of 200 µm) within 2 s. The use of 1251–1342 nm provided sufficient signal level and contrast required to visualize key cellular morphologic features. Conclusions: These preliminary results demonstrate that high‐speed SECM imaging of the human skin at 1251–1342 nm is feasible.